2014
DOI: 10.1155/2014/368274
|View full text |Cite
|
Sign up to set email alerts
|

The Spectrum of Anti-Chromatin/Nucleosome Autoantibodies: Independent and Interdependent Biomarkers of Disease

Abstract: Autoantibodies directed to chromatin components date back to the discovery of the LE cell and the LE cell phenomenon circa 1950, and subsequent evidence that major components of that reaction were chromatin components and histones in particular. Over time, immunoassays ranging from ELISA and line immunoassays to more modern bead-based assays incorporated histone and DNA mixtures, purified histones, and purified nucleosomes leading to a more thorough understanding of the genesis and pathogenetic relationships o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 185 publications
(226 reference statements)
2
21
0
Order By: Relevance
“…Serum autoantibodies and complement factors are widely used for measuring activity and diagnosing flares in SLE. 22 Antibodies to double-stranded DNA (anti-dsDNA) are found in approximately 50% of SLE patients, 23 and their serum levels correlate with lupus activity, especially nephritis. [24][25][26][27] However, the magnitude of this association varies significantly across different studies with positive likelihood ratios ranging from 0.88 to >10.…”
Section: Serological Tests In the Diagnosis Of Lupus Flarementioning
confidence: 99%
“…Serum autoantibodies and complement factors are widely used for measuring activity and diagnosing flares in SLE. 22 Antibodies to double-stranded DNA (anti-dsDNA) are found in approximately 50% of SLE patients, 23 and their serum levels correlate with lupus activity, especially nephritis. [24][25][26][27] However, the magnitude of this association varies significantly across different studies with positive likelihood ratios ranging from 0.88 to >10.…”
Section: Serological Tests In the Diagnosis Of Lupus Flarementioning
confidence: 99%
“…Since these early publications, there have been many published papers to support the importance of anti-dsDNA antibodies as a biomarker in the diagnosis, pathogenesis, and prognosis of SLE (reviewed in 2 , 13 , and 14 ).…”
Section: Historic Perspectivementioning
confidence: 99%
“…In the review by Mehra and Fritzler 14 , it was concluded that the anti-chromatin/nucleosome antibodies may be superior to anti-dsDNA antibodies as a biomarker for SLE. In summary, this brief analysis of the literature supports the conclusion that anti-dsDNA antibodies are not specific or the best biomarker for SLE.…”
Section: Anti-dsdna Antibodies Are Not Specific or The Best Biomarkermentioning
confidence: 99%
“…Similar observations are applicable to anti-nucleosome antibodies, a family of anti-chromatin antibodies, measured by solid phase assays using intact or H1-stripped nucleosomes that detect antibodies reactive with DNA, histones, or determinants formed by the association of DNA with histones [ 15 , 16 ]. Anti-nucleosome antibodies display a sensitivity and specificity similar to solid phase assays for anti-dsDNA antibodies, and similar correlations with disease activity and organ involvement in SLE.…”
Section: Introductionmentioning
confidence: 83%